2021
DOI: 10.4049/jimmunol.206.supp.16.21
|View full text |Cite
|
Sign up to set email alerts
|

The corruption of innate immunity by Streptococcus anginosus group

Abstract: Streptococcus anginosus group (SAG), formerly known as Streptococcus milleri, consists of three distinct streptococcal species: Streptococcus anginosus, Streptococcus constellatus, and Streptococcus intermedius. SAG was considered as commensal bacteria of colon, oral cavity and vagina. Recent observation reported those bacteria as potent pathogens found in brain or liver abscess. Mechanism of SAG pathogenesis is still unknown, despite the strong set of clinical data. In our study, we determined the virulence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It found that the strains’ virulence factors allowed bacteria to evade immune system elimination and allow it to colonize the body. 11 …”
Section: Discussionmentioning
confidence: 99%
“…It found that the strains’ virulence factors allowed bacteria to evade immune system elimination and allow it to colonize the body. 11 …”
Section: Discussionmentioning
confidence: 99%